Release of Platelet Factor 4 in Vivo during Intravascular Coagulation and in Thrombotic States - Farbiszewski, R; Niewiarowski, S; Worowski, K; Lipiński, B (Thrombosis and Haemostasis, 1968)
Platelet factor 4 released from platelets into the circulating blood was determined using both the heparin thrombin time and paracoagulation methods. It has been found that thrombin injected intravenously into rabbits releases large amounts of this factor. Infusion of plasmin does not release this factor and this finding may be of importance for the differential diagnosis between disseminated intravascular clotting and primary fibrinolysis. PF4 is not released during the hyper coagulable condition induced by HgCl2 intoxication. Only small amounts of this factor are released after contact factor infusion.A significant elevation of extraplatelet PF4 was found in 23 patients with fresh coronary thrombosis and in 9 patients with thrombophlebitis and thromboembolic complications.The significance of the above findings for the pathogenesis, treatment and laboratory diagnosis of thrombotic diseases with particular reference to heparin tolerance test is discussed.